1933 Haw. Sess. Laws 117 - (:unkn) unknown (My University, 1933)
No. 120, § 2: Prohibited a person, firm, or corporation from owning, possessing, selling, or transporting a machine gun, shell cartridge, or bomb containing or capable of emitting tear gas or other noxious gas.
Keywords: MACHINE GUN RESTRICTION